ANALISA PENGARUH BRAND EQUITY TERHADAP KINERJA KEUANGAN MELALUI CUSTOMER SATISFACTION SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN PERBANKAN DI SURABAYA - Artanta, Yustinus Priya (Business Accounting Review, 2016)
The purpose of this study was to examine the affet of brand equity on financial performance through customerâs satisfaction as an intervening variable on banking companies in Surabaya. Sample of this study were 35 bank companies in Surabaya. Data were collected by distributing questionnaires to the clients and also financial data of Indonesia Stock Exchange. This study used path modeling analysis technique with PLS tools. The Results showed that there were positive and significant affect of brand equity on customerâs satisfaction, positive and significant affect of brand equity on financial performance, and also positive and significant affect of costumerâs satisfaction on financial performance on bank companies in Surabaya.